PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN PADA APOTEK FIALIA FARMA KENDARI - Utha, Rasidin; Titop, Herman; Syuhraeni, Titik (Sultra Journal of Economic and Business, 2020)
This study aims to determine the influence of compensation on employee performance at the Fialia Farma Pharmacy Kendari. The number of respondents in this study were 7 people. The sampling technique uses census technique. Data analysis techniques were performed using simple linear regression. The results of this study indicate that compensation influences the performance of employees who work at the Fialia Farma Pharmacy Kendari.